2023
DOI: 10.3390/ph16050685
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and pH Environment of Foam Dressing Containing Eclipta prostrata Leaf Extract and Gelatin

Abstract: Eclipta prostrata (E. prostrata) has several biological activities, including antibacterial and anti-inflammatory activities, that improve wound healing. It is well known that physical properties and pH environment are crucial considerations when developing wound dressings containing medicinal plant extracts in order to create an appropriate environment for wound healing. In this study, we prepared a foam dressing containing E. prostrata leaf extract and gelatin. Chemical composition was verified using Fourier… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Supplementary Material shows all the FTIR spectra of the MSK and gelatin film dressings. Strong absorption bands appear at 1,630–1,634 cm −1 and 1,538–1,545 cm −1 due to the C=O and N-H/C-N bands in the gelatin [ 17 , 18 ]. In addition, a strong absorption band appears at 1,032–1,036 cm −1 due to the C-O-H band in the MSK [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementary Material shows all the FTIR spectra of the MSK and gelatin film dressings. Strong absorption bands appear at 1,630–1,634 cm −1 and 1,538–1,545 cm −1 due to the C=O and N-H/C-N bands in the gelatin [ 17 , 18 ]. In addition, a strong absorption band appears at 1,032–1,036 cm −1 due to the C-O-H band in the MSK [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results of chemical characterization found that there were decreased intensities in the absorption band of C=O (1,630-1,634 cm −1 ) and N-H/C-N (1,538–1,545 cm −1 ) in the MSK film dressings due to lower gelatin concentrations [ 17 ]. In contrast, increased intensities in the absorption band of C-O-H (1,032–1,036 cm −1 ) in the MSK film dressings due to higher MSK concentrations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%